The role of institutions in the corporate debt-productivity relationship: Evidence from listed firms in China - Chengchun Li; Huanhuan Lu; Min Wu; Da Teng (Journal of Applied Economics, 2023)
This paper examines the relationship between corporate debt and firm productivity. We add to the existing literature by investigating the contingency effect of institutional quality in the corporate debt-productivity nexus. Using data for 2,084 Chinese listed firms, we find that corporate debt and political institutional quality have significant and negative impacts on productivity while legal institutional quality is significantly and positively associated with productivity. Also, our results reveal that both financial and fintech-supporting institutional factors exert negative contingency effects in the corporate debt-productivity relationship. Our findings provide a reasonable guideline for emerging market countries aiming to address the corporate debt overhang problem or seeking factors to boost firm productivity growth.
Keywords: 330; corporate debt; debt overhang; firm productivity; institutional quality